PHDs inhibitor DMOG promotes the vascularization process in the AV loop by HIF-1a up-regulation and the preliminary discussion on its kinetics in rat - Yuan, Quan; Kneser, Ulrich (BMC biotechnology, 2014)
Background: The Arterovenous Loop (AV Loop) model is a vascularization model in tissue engineering research, which is capable of generating a three dimensional in vivo unit with cells as well as the supporting vessels within an isolation chmaber. In our previous studies the AV loop in the isolation chamber was discovered to undergo hypoxia, characterized by Hypoxia Inducible Factor (HIF) up-regulation. The vascularization followed the increase of HIF-α temporally, while it was spatially positively correlated with the HIF-α level, as well. This study aims to prove that HIF-1a up-regulation is the stimulus for vascularization in the AV loop model. Method: The AV loop model in rats was created by interposing a femoral vein graft into the distal ends of the contralateral femoral artery and vein, and the loop was embeded in fibrin matrix and fixed in isolation chamber. PHD (prolyl hydroxylases) inhibitor DMOG (Dimethyloxallyl Glycine) was applied systemically in the rats in 40 mg/KG at day 0 and day 3 (DMOG-1), or in 15 mg/KG at day 8, day10 and day12 (DMOG-2). Two weeks later the specimens were explanted and underwent morphological and molecular evaluations. Results: Compared to the control group, in the DMOG-2 group the HIF-1α positive rate was siginicantly raised as shown in immunohistochemistry staining, accompanied with a smaller cross section area and greater vessel density, and a HIF-1α accumulation in the kidney. The mRNA of HIF-1α and its angiogenic target gene all increased in different extends. Ki67 IHC demostrate more positive cells. There were no significant change in the DMOG-1 group. Conclusion: By applying DMOG systemically, HIF-1α was up-regulated at the protein level and at the mRNA level, acompanied with angiogenic target gene up-regulateion, and the vascularization was promoted correspondingly. DMOG given at lower dosage constantly after one week tends to have better effect than the group given at larger dosage in the early stage in this model, and promotes cell proliferation, as evidenced by Ki67 IHC. Thus, this study proves that HIF-1a up-regulation is the stimulus for vascularization in the AV loop model and that the process of the vessel outgrowth can be controlled in the AV Loop model utilizing this mechanism.
Gesehen am 09.11.2020